Produtividade de setores de tomografia computadorizada utilizando simulação por eventos discretos - Santos, Rogério Pires dos (2019)
Computed tomography (CT) is now one of the most important medical equipments for anatomical exams. This work studied 11 CT scanners of 1, 2, 4, 16 and 128 slices from 3 manufacturers in 10 health units. For that, we studied: CT market worldwide; opinions of professionals who manage CTs; examination procedures, steps and times. Then, 5 computer simulation models were created using the MedModel® software with 125 combinations of CT types, structures and patient demands, to study productivity, profitability, capacity, patients’ exam times and structural changes needed to optimize processes. The results showed that the CT scan time does not only depend on the time of image acquisition and that it does not become proportionally faster replacing a CT by one with capacity for more simultaneous slices. For example, the time of image acquisition in a brain scan made on an 1-slice CT took 2’15", while the same exam on an 128-slice CT took 1’37". The simulation (scenario 4, fifth model) showed that choosing a 4-slice CT would be the most profitable and faster option. Times of other steps should be considered and examination procedures optimized. The results obtained may be useful to health managers. The simulation proved to be an important tool for the analysis of processes and changes.